Designing Platformer Game using GameMaker Studio - Hadi, Ariesto (International Journal of Art, Design, and Metaverse, 2024)
Most people who design and make video games for a living have experienced that game development is less pretty than it seems. Timelines to meet, bottlenecks in production, pressure from video game publishers, and endless workweeks are just a few of the many challenges that arise during the development cycle. However, few who venture into game development know that culture and customs test one’s sincerity and determination, but the drive to produce video games that look, feel, and play beautifully keeps them going. In this study, we learn how to make games with GameMaker Studio. The games that you make are simple, namely maze and platformer games. The game’s object is to move the object through the maze to reach the endpoint. In this example, the player is Pitung, and the endpoint is to exit the yard through the gate. The walls of the labyrinth were made of walls and a few thick trees that made it impassable. Besides that, if you encounter dogs and Dutch soldiers on the road, Pitung will return to find another way.